Characteristics of Postpartum Mother with Perineum Scars at Trismalia Deli Serdang Clinic, 2020 - Mesrida Simarmata; Lisdayanti Simanjuntak (Science Midwifery, 2020)
The maternal mortality rate is still high, the causes of maternal death are mostly bleeding, infection, pre-eclampsia and eclampsia as well as unsafe abortion. One of the infections that can occur during the puerperium is the perineal wound that does not heal. Perineal wound is a wound that occurs during childbirth in the part between the vulva and rectum. The wound healing process can be accelerated by treating the wound using either medicine or herbs. Aim: to see the characteristics of postpartum mothers who have perineal injuries at the Trismalia Deli Serdang Clinic. Method: Deskriptif . The population of this study were 36 postpartum mothers with perineal injuries. Resulh: Education: majority of SMA 16 people (44.4%), Occupation: Majority of housewives 30 people (83, 3%), Age: 20-35 years 34 people (94.4%) Parity is 50% primigravida and 50% multiparous, Birth weight: the majority 2500-3000 grams Conclusion: Characteristics of postpartum mothers in the Trismalia Deli Serdang clinic who suffered injuries in terms of education, work, age, parity, Upper Arm Circumference. Suggestion: look for the relationship between education, occupation, age, parity, Upper Arm Circumference to perineal wound healing